Optimizing Mangrove Conservation through Integrated Landscape Management in Kota Karang, Bandar Lampung - Puang Nauli Tobing; Rizka Nabilah; Septi Maulidyah (Brawijaya University, 2023)
Mangrove degradation in Bandar Lampung, specifically Kota Karang, Teluk Betung Timur, has left only 9,86% or 6 hectares, causing habitat loss and increased greenhouse gas emissions. This study identifies deficiencies in the government-led mangrove management system, emphasizing individual management leading to overlapping responsibilities and a lack of coordination. The research method employed is descriptive qualitative, incorporating primary data from observations, interviews, and documentation, alongside secondary data and literature studies. Observations encompass the assessment of biophysical elements, ecological indicators, and mangrove reduction due to land conversion. Literature studies focus on identifying soil types, water pH, dissolved oxygen levels, mangrove vegetation types, and principles of integrated landscape management. SWOT (Strength, Weakness, Opportunity, Threats) analysis considers stakeholders roles, disaster risks, land conversion, pollution, over-exploitation, and community participation. Findings prompt five strategies: community empowerment, eco-friendly tourism, cross-sector cooperation, enhanced monitoring, and mangrove rehabilitation. Recommendations, rooted in integrated landscape management, target all stakeholders, with a focus on government involvement. This holistic approach addresses identified issues, striving for enhanced mangrove ecosystem sustainability through collaborative efforts and strategic planning, emphasizing the need for coordinated stakeholders action in mangrove conservation. Keywords: degradation, land conversion, stakeholders, SWOT analysis.